2016
DOI: 10.1128/mcb.01062-15
|View full text |Cite
|
Sign up to set email alerts
|

Calpain Genetic Disruption and HSP90 Inhibition Combine To Attenuate Mammary Tumorigenesis

Abstract: Calpain is an intracellular Ca 2؉ -regulated protease system whose substrates include proteins involved in proliferation, survival, migration, invasion, and sensitivity to therapeutic drugs. Genetic disruption of calpain attenuated the tumorigenic potential of breast cancer cells and hypersensitized cells to 17AAG, an inhibitor of the molecular chaperone HSP90. Calpain-1 or -2 overexpression rendered cells resistant to 17AAG, whereas downregulation or inhibition of calpain-1/2 led to increased cell death in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 48 publications
0
23
0
1
Order By: Relevance
“…Calpain‐1 is a Ca 2+ ‐dependent proteolytic enzyme that involves in protein degradation and various signaling pathways . Interestingly, various reports have indicated that HSP90 and calpain‐1 are involved in apoptotic process and many HSP90 client proteins are also calpain substrates . These findings further support the role of calpain‐1 as a novel partner of HSP90 to regulate cellular functions.…”
Section: Discussionmentioning
confidence: 61%
“…Calpain‐1 is a Ca 2+ ‐dependent proteolytic enzyme that involves in protein degradation and various signaling pathways . Interestingly, various reports have indicated that HSP90 and calpain‐1 are involved in apoptotic process and many HSP90 client proteins are also calpain substrates . These findings further support the role of calpain‐1 as a novel partner of HSP90 to regulate cellular functions.…”
Section: Discussionmentioning
confidence: 61%
“…Calpains-1/2 have been implicated in membrane-cytoskeletal dynamics associated with cell migration and invasion [ 18 , 32 ]. In vitro migration and invasion were both compromised by capns1 KO in mouse embryonic fibroblasts [ 15 , 17 ] or capns1 knockdown in MDA-MB-231 breast cancer cells [ 25 ]; and capn2 knockdown was associated with dysregulated focal adhesion turnover [ 18 ] and lamellipodia dynamics [ 16 ] in fibroblasts, as well as attenuated migration and invasion in mammary carcinoma cells [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have linked calpain to trastuzumab resistance in HER2 + breast cancer cells through generation of a p95HER2 fragment [ 19 , 24 ], or resistance to chemotherapeutics like doxorubicin through regulating multidrug resistance protein function [ 25 ]. Thus, a growing body of research suggests that inhibition of calpain may suppress tumorigenesis and could cooperate or synergize with specific existing treatments to improve breast cancer patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…To allow tumor progression and dissemination in the body, apoptosis resistance is a vital determinant (Jenning, Pham, Ireland, Ruoslahti, & Biliran, 2013). CAPNs are paradoxically associated with either prosurvival or prodeath efforts (Grieve et al, 2016). Researchers revealed that in colon cancer, stress-induced CAPN activation cleaves Myc into Myc-nick, an N-terminal truncation of Myc located in the cytoplasm, and has prosurvival and metastasis capacities (Conacci-Sorrell, Ngouenet, Anderson, Brabletz, & Eisenman, 2014).…”
Section: Apoptosismentioning
confidence: 99%